APPLICATION OF THE EDUCATIONAL TOURISM CONCEPT TO THE DESIGN OF THE ECO-PARK SCIENCE CENTER - Rizka Agusti Suciati; Etty Indrawati; Silia Yuslim (Universitas Trisakti, 2023)
Eco-park Science Center Cibinong was built in 2003 with the aim of ex-situ plant conservation activities, research, education, recreation, and environmental services. Initially, this area was an agricultural and plantation area belonging to the people. The current conditions at the Eco-park science center are planted with various vegetation according to the diversity of Indonesian ecosystem types based on bioregions. Bioregions are regional zone divisions representing each forest area in Indonesia, such as the Sumatra, Java-Bali, Nusa Tenggara, Kalimantan, Sulawesi, Maluku, and Papua/Irian Jaya bioregions. This area is not only used as a place to explore knowledge but also as a recreation area. The recreational area in Ecopark still needs to have adequate facilities. Though many come for recreation, this study aims to apply the concept of educational tourism to the Cibinong Center Eco-park area. This study uses a qualitative descriptive method grounded theory and explorative in the field. After the data is collected, then the data will be processed and classified compared to the study literature. The study results show that the concept of educational tourism, which includes the cognitive domain (understanding, knowledge), is contained in the area constructed wetland, green wall, rain garden, forest tower 1, forest walk, forest tower two, and waste processing. The Affective Domain (related to feelings and attitudes) is contained in the area viewing spots 1, 2, and 3, Plaza 2. Whereas the psychomotor domain (related to movement and involving the limbs) is contained in the area of the forest walk, Promenade 1, 2, and 3 as well Amphitheater.